DESCRIPTIVE STUDY OF HONORIFIC USE IN KOREAN EMAIL DISCOURSE - Kim, Jaegu (Indonesian Journal of Applied Linguistics, 2016)
It is a relatively new field that examines how Korean culture affects Korean language use in terms of age difference in a corpus of computer mediated email discourse. The purpose of this descriptive study and experiment is to prove the close relationship between Korean language and culture. This paper shows the descriptive study of Korean culture in relation to language use. Korean culture acknowledges an inherent hierarchy with regard to age, and considers [+age] as relating socially to [+power]. When younger Koreans converse with older ones, they express different morpho-syntactic patterns, which is an age complex. The main task of the experiment was to examine the way through which the age complex is reflected by Korean honorific linguistic system in email discourse. I asked 15 Korean native speakers between the ages of 20 to 25 to write emails expressing an impositive request to [+age (46-50 years old)], [-age (below 25 years old)] and [=age] recipients. The results show significant differences in the use of grammatical features in emails written to [+age] recipients, as compared to emails written to [-age] and [=age] recipients. The implication of the findings is that the cultural values that are attached to age and aging in the Korean society affects Koreans? language use, which means Korean language and culture are closely intermingled.